Value Type, Value Type Interaction, Conflict, and Conflict Management Style of House-Sharing Young Adults - Ardhiati, Agatha N.; Soewondo, Soesmalijah; Fausiah, Fitri (Faculty of Psychology, Universitas Surabaya, 2012)
House-sharing is often found in relatively expensive cities such as Jakarta. By sharing residence, individuals can save money on personal expenses and allocate itto meet other needs. The decision to live together, although made with full consideration including the value equation, differences between individuals are still inevitable, which can result in dispute or conflict. This study aims to obtain descriptions about value type, value type interactions, conflict, and conflict management style within these individuals. Hence, a mixed-method approach has been used with sequential explanatory strategy, which carried out the quantitative data collection and analysis using Schwartz Personal Value (SPV) questionnaire and the Thomas-Kilmann Instrument (TKI). Then a qualita- tive data collection and analysis was conducted. Participants were the occupants of two different residences. The results showed that the interaction between individual values may establish harmo- nious or conflicted relationships. Conflicts that arise from conflicting value types were managed by using different styles. Berbagi tempat tinggal (BTT) merupakan fenomena yang seringkali ditemukan di berbagai kota yang tergolong mahal seperti Jakarta. Dengan BTT, individu dapat menghemat pengeluaran pri- badi dan mengalokasikannya untuk memenuhi kebutuhan lain. Keputusan BTT, meskipun dibuat dengan penuh pertimbangan, termasuk persamaan nilai, perbedaan antarindividu pun tetap tak ter- elakkan, yang dapat berakibat perselisihan atau konflik. Penelitian ini bertujuan memperoleh gambaran tipe nilai, interaksi antartipe nilai, konflik, serta gaya pengelolaan konflik pada para individu tersebut. Untuk itu digunakan pendekatan mixed-method dengan strategi sequential explanatory, yaitu pengambilan data dan analisis secara kuantitatif menggunakan kuesioner Schwartz Personal Value (SPV) Questionnaire dan The Thomas-Kilmann Instrument (TKI). Kemudian dilakukan pengambilan data dan analisis secara kualitatif. Partisipan adalah para penghuni dua tempat tinggal yang berbeda. Hasil penelitian menunjukkan bahwa interaksi antartipe nilai individu dapat membentuk hubungan saling selaras maupun saling bertentangan. Konflik yang muncul akibat tipe nilai yang saling bertentangan dikelola menggunakan gaya yang berbeda.